Sistema de registro unico de historias clinicas, como soporte para la toma de decisiones para pacientes con enfermedades catastroficas basados en web services - Campoverde Vascones, Jimmy Campoverde (2011)
This project looks at the healt sector, improve processes, targeted efforts to research and development of applications, to provident significant benefcts to patients.